Baywatch [videorecording (DVD)] - Johnson, Dwayne, 1972-; Efron, Zac; Chopra Jonas, Priyanka; Anderson, Pamela, 1967-; Hasselhoff, David (Paramount Home Entertainment, 2017)
Devoted lifeguard Mitch Buchanan butts heads with a brash new recruit. Together, they uncover a local criminal plot that threatens the future of the Bay.